1997
DOI: 10.1161/01.atv.17.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hypercholesterolemia and Adventitial Inflammation on the Development of Aortic Aneurysm in Rabbits

Abstract: Abdominal aortic aneurysms are characterized by intimal atherosclerosis, disruption and attenuation of the elastic media, and a variable adventitial inflammatory infiltrate. We have developed an animal model of this disorder to evaluate the contribution of hypercholesterolemia, medial injury, and adventitial inflammation to aneurysmal dilatation. To accomplish this, we used periaortic application of calcium chloride, which induced both medial injury with calcification and endothelial injury. Ultrasonography wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
2
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 22 publications
1
53
2
3
Order By: Relevance
“…This information can be applied not only to domestic animals but also to humans (Cizkova et al, 2001). Furthermore, as an excellent model species, rabbits help to investigate such conditions like arterial injury (Jorgensen et al, 1972), aortic occlusion (Mackey et al, 1997) and aortic aneurysm (Freestone et al, 1997). However, there is limited information about basic anatomy of the rabbit kidney.…”
Section: Introductionmentioning
confidence: 99%
“…This information can be applied not only to domestic animals but also to humans (Cizkova et al, 2001). Furthermore, as an excellent model species, rabbits help to investigate such conditions like arterial injury (Jorgensen et al, 1972), aortic occlusion (Mackey et al, 1997) and aortic aneurysm (Freestone et al, 1997). However, there is limited information about basic anatomy of the rabbit kidney.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a wire injury model is used for studying pathology of endothelial injury/dysfunction [5]; low-density lipoprotein receptor-deicient mice [6] and apolipoprotein E-deicient mice [7] are commonly used as atherosclerosis models; calcium chloride [8], elastase [9], angiotensin II [10], or microRNA-21 [11] are infused to create an abdominal aortic aneurysms model. Developing a disease model occupies a great deal of scientiic indings on pathophysiology, and so the existing models should always open to be reined.…”
Section: Physiologic and Pathologic Angiogenesis -Signaling Mechanismmentioning
confidence: 99%
“…Hemorheology was assessed by measuring WBPT using an MC-FAN HR300 rheometer (MC Healthcare Inc., Tokyo, Japan), as previously reported [6,10]. The microchannel passage time for 100 µL of physiological saline as a control was initially measured, followed by that for 100 µL of heparinized blood samples obtained from the study participants.…”
Section: Assessment Of Hemorheology Using Mc-fanmentioning
confidence: 99%
“…MC-FAN has a simple methodology and is superior to other methods regarding the accuracy of channel dimensions and high reproducibility. Furthermore, some clinical studies have reported a significant relationship between an increase in the whole blood passage time (WBPT), which is measured using MC-FAN, and cardiovascular risk factors or coronary artery disease [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%